Kinetics and Mechanism of Oxidation of Methionine by Chloramine-T in Alkaline Medium in Presence of OsO4 Catalyst - Demappa, T.; Ananda, S. (Asian Journal of Chemistry, 2010)
Kinetics and mechanism of oxidation of D-L methionine (Met) by sodium N-chlorotoluene-p-sulphonamide (CAT) in alkaline medium in presence of OsO4 catalyst have been investigated at 30ºC, and the results are compared to the reaction without Os(VIII) catalyst. The reaction rate shows a first order dependence each on [CAT] and [methionine] and inverse fractional order on [OH–] and fractional order on [OsO4]. Additions of halide ions and variation of ionic strength and dielectric constant of the medium do not have any significant effect on the reaction rate. Thermodynamic parameters have been evaluated.